The Effect of Job Satisfaction and Work Environment on Employee Turnover Intention of PT Honda Forward Motor Tanjung Api-Api - M. Ferdi Saputra (International Journal of Marketing & Human Resource Research, 2021)
This study aims to analyze the effects of job satisfaction and work environment on the turnover intention of employees of PT Honda Maju Motor Tanjung Api-Api. A total of 101 samples were determined deploying the Slovin formula. Data were collected through questionnaires and analyzed using the multiple linear regression method. The results of the investigation exhibit that partially job satisfaction has no significant effect on turnover intentions. Conversely, the work environment has a significant and positive effect on turnover intention. Simultaneously, job satisfaction and work environment have a positive and significant effect on employees' turnover intention. This empirical finding can benefit PT Honda Maju Motor TanjungApi-Api. The leaders of the company should pay attention to satisfaction and work environment in their management because these two factors affect employees' turnover intention.